Deficits of psychomotor and mnesic functions across aging in mouse lemur primates - Languille, Solène; Liévin-Bazin, Agatha; Picq, Jean-Luc; Louis, Caroline; Dix, Sophie; De Barry, Jean; Blin, Olivier; Richardson, Jill; Bordet, Régis; Schenker, Esther; Djelti, Fathia; Aujard, Fabienne (Frontiers in Behavioral Neuroscience, 2015)
Owing to a similar cerebral neuro-anatomy, non-human primates are viewed as the most valid models for understanding cognitive deficits. This study evaluated psychomotor and mnesic functions of 41 young to old mouse lemurs (Microcebus murinus). Psychomotor capacities and anxiety-related behaviors decreased abruptly from middle to late adulthood. However, Mnesic functions were not affected in the same way with increasing age. While results of the spontaneous alternation task point to a progressive and widespread age-related decline of spatial working memory, both spatial reference and novel object recognition memory tasks did not reveal any tendency due to large inter-individual variability in the middle-aged and old animals. Indeed, some of the aged animals performed as well as younger ones, whereas some others had bad performances in the Barnes maze and in the object recognition test. Hierarchical cluster analysis revealed that declarative-like memory was strongly impaired only in 7 out of 25 middle-aged/old animals. These results suggest that this analysis allows to distinguish elder populations of good and bad performers in this non-human primate model and to closely compare this to human aging.